Słupsk’s Migration Narratives: Literary and Theatrical Contexts - Sobiecka, Anna (Porównania, 2022)
This article aims to describe narratives regarding migration within Slupsk's cultural sphere and their contextual reflections in theatre. The article begins with a comparative analysis of local biographies written down in personal documents, such as the yet-to-be-published Wspomnienia pierwszych słupszczan (“Memories of the first residents of Slupsk”), and the published accounts of Slupsk's residents in Mój nowy dom (“My new home”). The above works are then examined through the lens the of literary discourse surrounding migratory identity.